Closed Suction System terhadap Saturasi Pasca Operasi Jantung Bawaan (PJB) pada Anak - Ina Yuhana; Nani Nurhaeni (Journal of Telenursing (JOTING), 2021)
This study aims to identify the effect of a closed suction system on oxygen saturation in post-cardiovascular (CHD) patients. The method used is the electronic database literature search ScienceDirect, Clinical Key, Pro quest, EBSCO and Scopus by reviewing the results of previous studies in published articles using the keywords Pediatric AND Endotracheal Closed suction system AND saturation. The results of the analysis obtained the following themes: (1) desaturation; (2) pain; (3) cardiovascular instability; (4) saline instillation. In conclusion, the use of the open suction system method showed a decrease in SPO2 and an increase in Heart Rate (HR) and Mean Arterial Pressure (MAP) compared to the closed suction system method so that a closed suction system can be recommended in patients after congenital heart surgery (CHD). Keywords: Children, Closed Suction System, PJB, Saturation